Les logiques du marché à l'œuvre dans les dispositifs scolaires d'éducation au cinéma - Cédric Barbier; Tomas Legon; Lisa Marx; Anna Mesclon
This article revisits four independent studies on French cinema education programs Collège au cinéma (Middle school at the movies) and Lycéens au cinéma (High school at the movies). Including not only cultural institutions and schools but also the film industry, it shows that these programs are both based on and support actors from the field of restricted production in the film sector, thus creating an alternative market where certain beliefs are implicitly shared. Furthermore, the article analyzes the encounter between the films selected in the programs - largely classic or art-house movies - and the ordinary movie-going experiences of youth which are mostly linked to the field of large-scale production.